Identifikasi Daerah Resapan Air di Sub Daerah Aliran Sungai Malino Hulu Daerah Aliran Sungai Jeneberang Kabupaten Gowa - Wahyuni Wahyuni; Usman Arsyad; Budirman Bachtiar; Muhammad Irfan (Fakultas Kehutanan, Universitas Hasanuddin, 2017)
Population increase encourages people to change land use in Malino sub watershed. The forest area converted into non-forest areas such as agricultural or settlements. This study aims to determine the status and potential of water absorbtion region. This research was conducted in the Malino sub watershed maps using land units derived from overlapping maps of slope, soil type, rainfall and land use. Moreover, the determination of the water absorbtion region refer to the Technical Plan for Forest and Soil rehabilitation - basin. The results showed that up to 27,05% of the total Malino Sub Watershed is critical condition, normal condition as much as 49,70% and a good conditions as much as 23.25%. The Malino sub watershed still good potential to absorb water. In natural conditions, the use of land as dry bush agriculture to intervene it is advisable to agroforestry or timber planted with long lasting in order to be a good absorbtion region, while for normal condition advised to planting of agroforestry with pattern alley cropping.